UGC3:a covert communication method defense against censorship - Qing-feng TAN; Pei-peng LIU; Jin-qiao SHI; Xiao WANG; Li GUO (Tongxin xuebao)
A UGC-based covert communication method: UGC3was presented,which used fixed infrastructure (UGC sites) to form a fully distributed overlay.To exchange information between sender and receiver,an efficient resource discovery algorithm was proposed to negotiate the rendezvous; and then the targeted resource was published in the corresponding user-generated content hosts using information hiding method.Finally,the security properties were discussed.